Mitigating the Gridlock: A Hybrid VISSIM-Based Evaluation of Traffic Engineering and Demand Management Strategies for Urban Superblocks - Adie Kuntara; Abdullah Ade Suryobuwono; Rully Indrawan; Olfebri; Aswanti Setyawati (Green Publisher, 2026)
Urban superblocks integrating mixed-use developments generate substantial traffic volumes that threaten to overwhelm existing arterial networks in rapidly urbanizing cities. This study evaluates the operational traffic impacts of the Pakuwon superblock development in Bekasi, Indonesia, using PTV VISSIM microsimulation calibrated against Indonesian Road Capacity Guidelines (PKJI 2023). The research employs a hybrid methodology combining traffic engineering interventions with transportation demand management (TDM) strategies following the Avoid-Shift-Improve (ASI) framework. Baseline simulations reveal catastrophic network failure without mitigation, with volume-to-capacity (V/C) ratios reaching 1.81 and Level of Service (LOS) F on critical arterial segments. The study tested four alternative scenarios, with Alternative 3 (flyover construction combined with comprehensive TDM measures achieving 10% private vehicle reduction) demonstrating optimal performance. Post-mitigation simulations show V/C ratios reduced to 0.69 (average 47% improvement), speeds increased by 36%, and LOS improved to C-D across all segments. Findings demonstrate that integrating physical infrastructure improvements with binding demand management policies is essential for sustainable urban development in congested Asian cities. The research contributes a replicable methodological framework for traffic impact assessment that transcends conventional geometric-only approaches.